2023
DOI: 10.3389/fonc.2023.1216852
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment lymphocyte-to-monocyte ratio as a prognostic factor and influence on dose-effect in fractionated stereotactic radiotherapy for oligometastatic brain metastases in non-small cell lung cancer patients

Abstract: BackgroundStudies on the prognostic factors for patients with brain oligo-metastasis treated with fractionated stereotactic radiotherapy (FSRT) usually focus on the size of metastatic tumor and radiation dose. Some inflammatory indicators have predictive value in non-small cell lung cancer (NSCLC) with brain metastasis receiving stereotactic radiotherapy. However, the prognostic value of inflammatory indicators in NSCLC patients with brain oligo-metastasis treated with FSRT, and their effect on radiotherapy do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Current evidence shows that chronic inflammation is inseparable from tumorigenesis, proliferation, infiltration, metastasis, and apoptosis at various stages [ 4 , 5 ]. Recent studies have demonstrated that diverse blood-based inflammation parameters, such as platelet-to-lymphocyte ratio [ 6 ], lymphocyte-to-monocyte ratio [ 7 ], C-reactive protein-to-albumin ratio [ 8 ], prognostic nutritional index [ 9 ], and systemic inflammation response index (SIRI) [ 10 ] have significant value in predicting the prognosis of many solid tumors. The SIRI can be determined as SIRI = neutrophil count × monocyte count/lymphocyte count.…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence shows that chronic inflammation is inseparable from tumorigenesis, proliferation, infiltration, metastasis, and apoptosis at various stages [ 4 , 5 ]. Recent studies have demonstrated that diverse blood-based inflammation parameters, such as platelet-to-lymphocyte ratio [ 6 ], lymphocyte-to-monocyte ratio [ 7 ], C-reactive protein-to-albumin ratio [ 8 ], prognostic nutritional index [ 9 ], and systemic inflammation response index (SIRI) [ 10 ] have significant value in predicting the prognosis of many solid tumors. The SIRI can be determined as SIRI = neutrophil count × monocyte count/lymphocyte count.…”
Section: Introductionmentioning
confidence: 99%